Sesquiterpenoids from the roots of Croton crassifolius. Issue 7 (3rd July 2019) - Tian, Jin-Long; Li, Chen-Xi; Shang, Xin-Yue; Hou, Xue-Wen; Zhang, Yan; Li, Ling-Zhi; Huang, Xiao-Xiao; Song, Shao-Jiang
Abstract: Phytochemical investigation of Croton crassifolius roots afforded five sesquiterpenes (1–5 ), including two new sesquiterpenes 6 S -hydroxy-cyperenoic acid (1 ) and crassifterpenoid A (5 ), together with three known compounds (2–4 ). The structures of the new compounds were determined by comprehensive spectroscopic methods, and their absolute configurations were determined by quantum chemical ECD calculation. Crassifterpenoid A (5 ) is the first germacrane-type sesquiterpene isolated from C. crassifolius, which enriched the diversity of chemical constituents in Croton crassifolius . In addition, the cytotoxicities of all compounds against human liver cancer lines HepG2 and Hep3B were determined, but none showed significant activity. Abstract :